Implementation of Education Financing Management at SMA Darussalam Blokagung Banyuwangi - Huzali, Ikhsan; Al Fawaz, Ahmad Hadiq Syifa’; Ekaningsih, Lely Ana Ferwati; Rungkittanasan, Nakorn (Electronic Journal of Education, Social Economics and Technology, 2024)
Successful educational institutions cannot be separated from the support of adequate education costs, because in essence the quality of education will be directly proportional to the amount of education costs incurred, the higher and more expensive the education costs used and incurred, the better the educational services will be and able to produce quality graduates with high learning outcomes. It seems that it will be difficult to realize a good quality of education if it is not supported by sufficient education costs for operations. The results of the research on the implementation of education financing management at SMA Darussalam Blokagung Banyuwangi. This research uses a qualitative approach. Data collection techniques through observation, interviews and document studies. The results of the study show that education financing management in the school is implemented in the scope, including: (1) Implementation of the Preparation of the School Expenditure Budget Plan (RAPBS), (2) Implementation of financial management, (3) Evaluation of financial management.